Indeks Subjek Volume 35, Tahun 2015 - Indeks Subjek Volume 35, Tahun 2015 (agriTECH, 2015)
A spore forming bacteria 301Aceh 288Acid 332Acid hydrolysate 396Active compound 316Active edible coating 61Aflatoxin B 10Agitated fermentation 434AHP 223Akway 170Amylograph 324Animal 164Anthoecyanin 130Anti Aflatoxin 10Antibacterial 170Antimicrobial 44, 147Antioxidant 368Arabic gum 414Asam drien 288Aspergillus flavus 10Aspergillus oryzae 316Autism 212Autonomous tractor 106Autoregressive Integrated MovingAverage (ARIMA) 241Artificial Neural Network (ANN) 241